Rehabilitation Treatment with Plural Fixed Prosthesis Supported on Two Osseointegration Implants in Anterior Sector Toothless Patient (International Journal of Medical and Surgical Sciences, 2015)
A case of a man 44 years in dental clinics attended at the Universidad Autónoma de Chile, Temuco, which has no central and lateral incisors of both jaws occurs. In the first instance the anterior maxilla was rehabilitated through plural supported fixed prostheses four units on two implants osseointegrated in the space of the upper lateral incisors (absent).